2018
DOI: 10.1007/978-3-319-91689-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Taxonomy of Birds: The Nature and Delimitation of Species

Abstract: Species are the basic currency in biodiversity studies, but what constitutes a species has long been controversial. Since the late 1990s, debates over species have shifted from theoretical questions (e.g., What is a species? Which species concept is best?) to empirical questions (How can we document species both efficiently and accurately?). A growing number of taxonomists agree that species can be discovered and documented in many different ways, preferably by employing and combining multiple types of evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 119 publications
2
21
0
Order By: Relevance
“…Unless it can be shown that gene flow among adjacent lineages is restricted to narrow contact zones, by integrating phylogeographic structure with male's plumage variation (Kayvanfar et al., 2017), and taking into account the common pheasant lineages’ comparatively young ages (cf. Price, 2008), the evolutionary diversification is better reflected by splitting it into three species‐level taxa applying a more integrative approach towards species delimitation (Sangster, 2018): Yunnan pheasant P . elegans , Chinese pheasant P .…”
Section: Resultsmentioning
confidence: 99%
“…Unless it can be shown that gene flow among adjacent lineages is restricted to narrow contact zones, by integrating phylogeographic structure with male's plumage variation (Kayvanfar et al., 2017), and taking into account the common pheasant lineages’ comparatively young ages (cf. Price, 2008), the evolutionary diversification is better reflected by splitting it into three species‐level taxa applying a more integrative approach towards species delimitation (Sangster, 2018): Yunnan pheasant P . elegans , Chinese pheasant P .…”
Section: Resultsmentioning
confidence: 99%
“…This latitudinal pattern in the distribution of species within functional groups is likely to remain similar for both birds and bivalves through the discovery of new species and further sampling. Birds and bivalves are most thoroughly described and sampled in temperate regions ( particularly the north temperate) relative to tropical regions [19,45], suggesting the temperate values of FE are likely stable. The discovery and splitting of taxa in birds and bivalves will likely increase the species richness of tropical locales (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…To address the inherent subjectivity of assigning taxonomic rank to allopatric forms (Patten 2015), we followed the integrative taxonomic system based on phenotypic differentiation (Tobias et al 2010, Sangster 2018). Briefly, we scored differentiation in biometrics, acoustics, colour of plumage, ecology and behaviour, and geographic relationships.…”
Section: Methodsmentioning
confidence: 99%